Enhanced catalytic performance of palladium nanoparticles supported on novel N and F co-doped bio-carbon material for 5-hydroxymethylfurfural conversion - Dandan Li; Feichao Miao; Jinhua Chen; Zhibing Liu; Zhiyuan Wang; Yang Wang (PLoS ONE, 2025)
A novel N, F-co-doped bio-carbon material derived from cellulose was successfully developed via a convenient and simple strategy. The obtained bio-carbon material was characterized with various techniques. It is found that the addition of N, F precursors can benefit the formation of porous structure in bio-carbon during thermal pyrolysis and N, F dopants have significant effect on electronic structure of native carbon atoms, which could regulate the adsorption property and catalytic activity of obtained bio-carbon material. Furthermore, Pd NPs supported on the N, F-co-doped bio-carbon showed excellent catalytic activity and selectivity toward the aerobic oxidation of biomass-derived 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid in aqueous media under mild conditions. N, F dopants on bio-carbon material played an important role in the oxidation reaction.